PENGARUH BUDAYA ORGANISASI, KOMUNIKASI, KOMPENSASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN RUMAH SAKIT ASSALAM DI GEMOLONG KABUPATEN SRAGEN - -, Savitri (Universitas Slamet Riyadi, 2015)
The purpose of this study was to examine the Influence of Organizational Culture, Communication, Compensation and Work Discipline on Employee Performance RS Assalam Holy District. This research is the census. The data used are primary data by taking a sample of a population of 60 (sixty) respondents. This study uses analysis tools such as validity, reliability test, test multiple linear regression analysis, t test, F test and test coefficient determination (R2). Validity and reliability testing done by using one-shot methods to get the result that all the items declared valid and reliable. T test results showed that the Organizational Culture, Compensation and Work Discipline positive and significant impact on the performance communication while having a positive effect but no significant effect on performance. F test showed that the Organizational Culture, Communication, Compensation and Work Discipline simultaneously affect performance. the results showed that the coefficient of determination of 0,855 or 85,5 percent, which means that the variability of performance variables that can be explained by the variability of the variable Organizational Culture, Communication, Compensation and Work Discipline 85,5 percent while the remaining 14,5 percent is explained by other variables not included for example, a variable in the regression model of leadership, education and training, work environment and others. The most dominant variable is a discipline on the performance of work which can be proved by the greatest regression coefficient is 0,388 compared to other variables. Keywords: Organizational Culture, Communication, Compensation, Work Discipline, Performance